Gangguan Magnetik dan Elektrik Akibat Perambatan Gelombang Tsunami - arianto, Fadia shifa; Fahmi, Muhammad Nurul; Realita, Arie (Prodi Fisika FMIPA Universitas Negeri Surabaya, 2025)
This research aims to study electromagnetic disturbances as the generation of secondary magnetic field signals and total electron content (TEC) variations in the ionosphere due to major trans-Pacific tsunamis. Analysis was conducted on three major tsunami events, namely Hunga Tonga 2022, Tohoku 2011, and Chile 2010. Magnetic disturbance data were obtained using three main parameters taken from the official NOAA website. The data was then compared with the observations from the global INTERMAGNET magnetic stations. Meanwhile, the electrical disturbance data was obtained through GNSS-TEC satellite observations. The data obtained is then processed using statistical methods and signal observation to detect anomalies before and during a tsunami. The analysis results show a high level of agreement in bz values between the analytical estimates and observations. In the Tonga tsunami 2022, the difference ranged from 0.04-0.60 nT; Tohoku 2011 ranged from 0.00-0.90 nT; and Chile 2010 ranged from 0.00-0.06 nT. Additionally, TEC variations show significant disturbances in the ionosphere, with decreases and fluctuations in TEC values detected from before to several hours after the tsunami event. These findings confirm that tsunamis, whether triggered by earthquakes or volcanic eruptions, can produce measurable electromagnetic disturbances, and have the potential to be utilized for preliminary studies of early disaster detection systems.